Targeting CEACAM5-positive solid tumors using NILK-2401, a novel CEACAM5xCD47 κλ bispecific antibody - Seckinger, Anja; Buatois, Vanessa; Moine, Valéry; Daubeuf, Bruno; Richard, Françoise; Chatel, Laurence; Viandier, Alizée; Bosson, Nicolas; Rousset, Emeline; Masternak, Krzysztof; Salgado-Pires, Susana; Batista, Claudia; et al. (Frontiers in Immunology, 2024)
Background Blocking the CD47 “don’t eat me”-signal on tumor cells with monoclonal antibodies or fusion proteins has shown limited clinical activity in hematologic malignancies and solid tumors thus far. Main side effects are associated with non-tumor targeted binding to CD47 particularly on blood cells. Methods We present here the generation and preclinical development of NILK-2401, a CEACAM5×CD47 bispecific antibody (BsAb) composed of a common heavy chain and two different light chains, one kappa and one lambda, determining specificity (so-called κλ body format). Results NILK-2401 is a fully human BsAb binding the CEACAM5 N-terminal domain on tumor cells by its lambda light chain arm with an affinity of ≈4 nM and CD47 with its kappa chain arm with an intendedly low affinity of ≈500 nM to enabling tumor-specific blockade of the CD47-SIRPα interaction. For increased activity, NILK-2401 features a functional IgG1 Fc-part. NILK-2401 eliminates CEACAM5-positive tumor cell lines (3/3 colorectal, 2/2 gastric, 2/2 lung) with EC50 for antibody-dependent cellular phagocytosis and antibody-dependent cellular cytotoxicity ranging from 0.38 to 25.84 nM and 0.04 to 0.25 nM, respectively. NILK-2401 binds neither CD47-positive/CEACAM5-negative cell lines nor primary epithelial cells. No erythrophagocytosis or platelet activation is observed. Quantification of the pre-existing NILK-2401-reactive T-cell repertoire in the blood of 14 healthy donors with diverse HLA molecules shows a low immunogenic potential. In vivo, NILK-2401 significantly delayed tumor growth in a NOD-SCID colon cancer model and a syngeneic mouse model using human CD47/human SIRPα transgenic mice and prolonged survival. In cynomolgus monkeys, single doses of 0.5 and 20 mg/kg were well tolerated; PK linked to anti-CD47 and Fc-binding seemed to be more than dose-proportional for Cmax and AUC0-inf. Data were validated in human FcRn TG32 mice. Combination of a CEACAM5-targeting T-cell engager (NILK-2301) with NILK-2401 can either boost NILK-2301 activity (Emax) up to 2.5-fold or allows reaching equal NILK-2301 activity at >600-fold (LS174T) to >3,000-fold (MKN-45) lower doses. Conclusion NILK-2401 combines promising preclinical activity with limited potential side effects due to the tumor-targeted blockade of CD47 and low immunogenicity and is planned to enter clinical testing.